Determinasi Kemampuan Auditor dalam Mendeteksi Kecurangan: (Studi pada Inspektorat Provinsi Jawa Tengah) - Saifudin Saifudin; Bella Aprilia (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Institut Teknologi dan Bisnis (ITB) Semarang, 2019)
The aim of this research is to explole the perception of auditors in local government agencies on the effects of Professional Skepticism, Independence, Competence and Experience against Auditor’s Ability to Detect Fraud.The research of this population is auditors working on Inspektorat Provinsi Jawa Tengah. This research is populatif, which mean it doesn’t any sampling. Respondents in this research are 35 data collection using questionnaires the influence of independent variables such as : Professional Skepticism, Independence, Competence and Experience against Auditor’s Ability to Detect Fraud examined using multiple linear regression analysis by using SPSS 20.0. The results of this research indicates that Professional Skepticism, Independence, Competence and Experience affect against Auditor’s Ability to Detect Fraud.